2021
DOI: 10.18203/issn.2455-4529.intjresdermatol20213343
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of steroid modified tinea in pediatric age group at tertiary centre in North India

Abstract: <p class="abstract"><strong>Background:</strong> Uncontrolled use and abuse of topical steroids has led to increase in number of cases of superficial dermatophytosis of skin, hair and nail in pediatric age group as well. Our study aimed to analyse epidemiological and microbiological profile of steroid modified tinea (SMT) in pediatric age group.</p><p class="abstract"><strong>Methods:</strong> Clinically diagnosed tinea childhood patients with history of usage of topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
4
2
0
Order By: Relevance
“…Priyanka et al 25 in Chidambaram reported that patients of 15–50 years constituted >50% of the total study population. In our observational study, males ( n = 92, 54%) outnumbered females ( n = 78, 46%), which was in line with the study conducted by Chaudhary et al, 23 Monisha et al, 24 Thakur et al, 26 and differs slightly from the study by Priyanka et al 25 where they reported female preponderance. Male preponderance can be explained by many factors like excessive sweating, occlusive clothing, hormonal influence, and increased exposure to various environmental triggers.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Priyanka et al 25 in Chidambaram reported that patients of 15–50 years constituted >50% of the total study population. In our observational study, males ( n = 92, 54%) outnumbered females ( n = 78, 46%), which was in line with the study conducted by Chaudhary et al, 23 Monisha et al, 24 Thakur et al, 26 and differs slightly from the study by Priyanka et al 25 where they reported female preponderance. Male preponderance can be explained by many factors like excessive sweating, occlusive clothing, hormonal influence, and increased exposure to various environmental triggers.…”
Section: Discussionsupporting
confidence: 91%
“…These findings correlate with a study conducted by Monisha et al, 24 where they reported middle‐class strata being the highest. Close contact history was positive for 53% of patients among which 48% had a positive family history which is in line with findings from the study by Chaudhary et al, 23 where 52.5% family history was reported. In our study, the most common complaint reported by the patients was itching (82%), which is in concordance with the study by Chaudhary et al, 23 and Priyanka et al, 25 (83.64%) but it is slightly contrast to the study by Monisha et al, 24 where burning sensation (37%) and itching (34%) was highly reported.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations